IMPLICATION OF BUREAUCRATIC REFORM POLICY IN ECHELON III AND IV IN THE ENVIRONMENTAL SERVICES OFFICE OF BLORA REGENCY - Adi Purwanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of regional autonomy is to prosper the community by providing good public services to the community. In providing services to the public, the government uses bureaucracy. Bureaucracy thus requires employees with integrity, honesty, and capable. Along with the increasing demands and expectations of the people, the government needs to reform the bureaucracy by removing Echelon III and IV. The aim is for efficiency, effectiveness, and speed in decision making. This new policy makes uncertainty the fate of Echelon III and IV officials. This study aims to find out more deeply about Echelon III and IV reforms at the Environmental Services of Blora Regency. Researchers used descriptive qualitative methods. From the research findings, it was concluded that: a. intensive and dialogical socialization is needed; b. echelon officials who have already approached retirement age, resign themselves to government policies regarding the elimination of echelon III and IV; c. Echelon officials who are young and productive, prefer structural positions because structural positions will get more facilities and welfare than functional positions; d. staff who have the potential, diligently follow the training and have a visionary view, prefer functional positions because if you can meet the credit score, can be promoted faster, and impact on income will increase.